2014
DOI: 10.1002/2014wr015809
|View full text |Cite
|
Sign up to set email alerts
|

The pronounced seasonality of global groundwater recharge

Abstract: Groundwater recharged by meteoric water supports human life by providing two billion people with drinking water and by supplying 40% of cropland irrigation. While annual groundwater recharge rates are reported in many studies, fewer studies have explicitly quantified intra-annual (i.e., seasonal) differences in groundwater recharge. Understanding seasonal differences in the fraction of precipitation that recharges aquifers is important for predicting annual recharge groundwater rates under changing seasonal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
245
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 298 publications
(284 citation statements)
references
References 174 publications
19
245
0
4
Order By: Relevance
“…However, if the location of accumulated snow is far away from channels, or the snowfall amount is large, it will take longer for meltwater to run off than the frozen soil thaws. In these cases, a part of snow infiltrates into the ground and later is available for evaporation (Dripps, 2012;Jasechko et al, 2014). In fact, it may be more suitable to introduce as effective available water for evapotranspiration, where k is a loss parameter requiring further investigation.…”
Section: Limitation Of Revised Budyko Frameworkmentioning
confidence: 99%
“…However, if the location of accumulated snow is far away from channels, or the snowfall amount is large, it will take longer for meltwater to run off than the frozen soil thaws. In these cases, a part of snow infiltrates into the ground and later is available for evaporation (Dripps, 2012;Jasechko et al, 2014). In fact, it may be more suitable to introduce as effective available water for evapotranspiration, where k is a loss parameter requiring further investigation.…”
Section: Limitation Of Revised Budyko Frameworkmentioning
confidence: 99%
“…7). Seasonally higher recharge in spring for the basins could be due to additional sources of snowmelt from winter (DJF) P which tend to melt at the beginning of spring when temperature is sufficient to melt but not high enough to lose a lot of water from evaporation (Dunne and Leopold, 1978;Clark and Fritz, 1997;Ajami et al, 2012;Jasechko et al, 2014) in addition to rain occurring in spring time. Several field monitoring studies in Sweden (Rodhe, 1981), Idaho (Flerchinger et al, 1992), and the United States mid-west (Delin et al, 2007;Dripps, 2012) have also found that the spring snowmelt constitutes the bulk of annual groundwater recharge at the middle latitudes examined here.…”
Section: Seasonality Of Rechargementioning
confidence: 99%
“…Seasonal snowpack provides predictable melt timing and volumes in the spring, which influences streamflow timing, surface water and groundwater availability (Berghuijs et al, 2014;Jasechko et al, 2014;Stewart et al, 2005). Reliable spring snowmelt also provides a strong control on vegetation phenology and productivity in many 20 ecosystems (Parida and Buermann, 2014;Trujillo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%